TINJAUAN YURIDIS TERHADAP PRAKTEK INSIDER TRADING DALAM PASAR MODAL INDONESIA - Sere Intan A.Sinaga; Hardi '; Rahmad Hendra ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
ABSTRACTIndonesia is a development country which has improvement in many departments. The development in entrepreneurship is one factor concerned to development succeed. Through investing in capital market, business can improve continuously because it can accept fund from the investors. The implementation of openness principle is needed to keep capital market stable. Infraction to openness principle causes practice of insider trading. Prohibition to insider trading has deal with the improvement of capital market because it depends to the investors’ beliefs who invest in stock which issued by public corporate. The beliefs of the investors can be influenced by conspiracy of insiders to achieve advantages. Laws No.8 by 1995 about Capital Market in chapter 95-98 has arranged the prohibition insider trading practice. But in fact it still happened in public company which impact financial lost to investors, public corporate, even capital market. This research purpose to analyze normatively how characterized insider trading, and how the protection issue to the investors in the case of insider trading practice.Through this problem research, I have found two main points concluded. First, arrangement of characterized insider trading in Capital Market Laws does not appropriate and not capable to deceive doer so that this practice might happen to public corporate. Second, the prohibition to insider trading which in Capital Market Laws is still not able to give a complete protection to the investors because insider trading can be maximized.I suggest, first, we need a specific law about insider trading in Indonesia, for instance the arrangement of insider trading which owned by United States of America. This arrangement works to deceive doer and to keep investors trust in capital market. Second, to protect the investors from insider trading practice, it is needed to form a specific court in capital market to solve insider trading practice and also to give education about capital market to maintenance the law institution so that can make an easier way in maintenance the laws because by the effective law maintenance is a kind of protection to the investors.Keywords: observation- insider trading-capital market